Human rights and corruption: problems and potential of individualizing a systemic problem - Peters, Anne (International journal of constitutional law, 2024)
This article examines the advantages and challenges of a deliberate legal-political strategy that addresses corruption at an individual, rather than systemic, level. Empirical research has highlighted the correlations between the extent and nature of corruption and the level of human rights enjoyment. In response to these observations, anti-corruption and human rights policy agendas have been converging at the international and regional levels. However, framing corruption as a human rights violation that incurs international state responsibility poses conceptual difficulties. Additionally, the risks and benefits of this convergence need to be assessed. This article concludes that the human rights approach provides significant added value, outweighing its limitations. Yet, it remains an open question whether human rights are the appropriate normative framework for denouncing and combating corruption. The article suggests that the human rights perspective, by opening up new avenues for monitoring and litigation, effectively supplements the criminal law approach. It argues for a more balanced integration of corruption concerns within human rights frameworks, with equal emphasis on human rights considerations in all anti-corruption monitoring schemes. Such integration would likely foster a positive feedback loop, where anti-corruption efforts enhance human rights conditions, while certain human rights facilitate the fight against corruption.